(untitled) (Educational Knowledge, 2016)
One of the goals of early childhood education is to prepare children through readiness activities so they can learn to read and write. This process encompasses a series of methods, techniques, and strategies to guide students toward achieving this goal; however, in the public sector, only the basics of letters and reading are addressed. In contrast, in the private sector, students in the preparatory section progress to the next educational level already reading and writing. Currently, teachers who educate young children still rely on traditional methods for literacy instruction. While it is important to mention that Information and Communication Technologies (ICTs)[1] have been incorporated in recent years to support and innovate learning, it should be noted that private institutions have greater access to technological equipment than public institutions. Nevertheless, teachers in the latter are making efforts to incorporate and utilize these technologies in their classes. Furthermore, the research achieved the objectives of identifying, describing, and evaluating the methodological strategies and resources that preschool teachers implement using ICT in the literacy process, as well as evaluating the curricular integration of these technologies within the process. Finally, it adopted an explanatory-descriptive approach, as its purpose was to explain the conditions under which ICT is used to support literacy instruction.